Geospatial assessment of water quality using principal components analysis (PCA) and water quality index (WQI) in Basho Valley, Gilgit Baltistan (Northern Areas of Pakistan) - Fatima, Syeda Urooj; Khan, Moazzam Ali; Siddiqui, Farhan; Mahmood, Nadeem; Salman, Nasir; Alamgir, Aamir; Shaukat, Syed Shahid (Environmental monitoring and assessment, 2022)
Public health quality in Gilgit Baltistan (GB) is at threat due to multiple water-borne diseases. Anthropogenic activities are accelerating the burden of pollution load on the glacio-fluvial streams and surface water resources of Basho Valley in Skardu district of GB. The present research has investigated the drinking water quality of the Basho Valley that is being used for domestic purposes. The study also comprehends public health status by addressing the basis drinking water quality parameters. A total of 23 water samples were collected and then analyzed to elucidate the current status of physico-chemical, metals, and microbial parameters. Principal component analysis (PCA) was applied and three principal components were obtained accounting 53.04% of the total variance, altogether. PCA identified that metallic and microbial parameters are the major factor to influence the water quality of the valley. Meanwhile, water quality index (WQI) was also computed and it was observed that WQI of the valley is characterized as excellent in terms of physico-chemical characteristics; however, metals and microbial WQI shows most of the samples are unfit for drinking purpose. Spatial distribution is also interpolated using the Inverse distance weight (IDW) to anticipate the results of mean values of parameters and WQI scores. The study concludes that water quality is satisfactory in terms of physico-chemical characteristics; however, analysis of metals shows that the concentrations of copper (Cu) (0.40 ± 0.16 mg/L), lead (Pb) (0.24 ± 0.10 mg/L), zinc (Zn) (6.77 ± 27.1 mg/L), manganese (Mn) (0.19 ± 0.05), and molybdenum (Mo) (0.07 ± 0.02 mg/L) are exceeding the maximum permissible limit as set in the WHO guidelines for drinking water. Similarly, the results of the microbial analysis indicate that the water samples are heavily contaminated with fecal pollution (TCC, TFC, and TFS > 3 MPN/100 mL). On the basis of PCA, WQI, and IDW, the main sources of pollution are most likely to be concluded as the anthropogenic activities including incoming pollution load from upstream channels. A few underlying sources by natural process of weathering and erosion may also cause release of metals in surface and groundwater. This study recommends ensuring public health with regular monitoring and assessment of water resources in the valley.